ANALISIS KELAYAKAN PEMBANGUNAN JALAN DARI LIWAS - RING ROAD 2 KOTA MANADO - Royner Tarek,; Morris S Tumanduk,; Toar U.Y Pangkey, (Sustainable Construction (SUSCON), 2024)
Manado City, as the capital of North Sulawesi, continues to experience rapid growth, impacting the development of Paal 2 sub-district and Ranomuut Village as supporting areas. The increasing population density on the coast of Manado, where people work in the city center, has led to local and regional traffic problems. The impact is evident in congestion at various points on the main roads, contributing to high economic costs. The primary activities in Manado are concentrated in the Sario and Wenang districts, with Tikala district serving as the administrative center. However, traffic issues become more complex with two main arterial routes connecting Manado, located in Paal Dua and Malalayang districts, potentially causing traffic congestion during peak hours. The growth in the number of motorized vehicles flooding the main arterial roads demands a performance analysis to evaluate the capacity and efficiency of the road system. This research aims to analyze the performance of the main arterial roads in Manado, particularly in Paal Dua and Malalayang districts. Utilizing the road feasibility analysis method, this study will assess whether the existing arterial roads can accommodate current and future traffic flow. The results of the analysis will serve as a basis to determine the necessity of constructing new alternative roads to address the congestion of local and regional traffic, with the hope of reducing congestion and optimizing mobility in Manado City